Asymmetric synthesis of a 12-membered macrolactone core and a 6-epi analogue of amphidinolide W from 4-pentenoic acid - Chatterjee, Bhaskar; Mondal, Dhananjoy; Bera, Smritilekha (Tetrahedron-Asymmetry, 2012)
A flexible and efficient asymmetric route to the synthesis of a 12-membered macrolactone core and a 6-epi analogue of amphidinolide W has been accomplished from commercially available 4-pentenoic acid. The successful generation of stereocenters was achieved by utilizing an Evans' chiral auxiliary-based alkylation and aldol reaction. Other key reactions such as a Julia-Kocienski olefination, Kita's macrolactonization, ring closing metathesis (RCM) reaction, and Yamaguchi's esterification were significant for the construction of the macrolactone cores. (c) 2012 Elsevier Ltd. All rights reserved.